The influence of principal instructional leadership and school environment on teacher services of public junior high school - Agusli, Agusli; Gistituati, Nurhizrah; Hadiyanto, Hadiyanto; Jasrial, Jasrial (Indonesian Research Journal in Education |IRJE|, 2026)
This research aimed to analyze the influence of instructional leadership and the school environment on teachers’ teaching service at State Junior High School in Pasaman Barat Regency, West Sumatra. Using a quantitative correlational research design, data were collected through Likert-scale questionnaires from a sample of 156 teachers selected by stratified proportional random sampling. Descriptive statistics, simple regression, and multiple regression were employed to test the research hypotheses. The results indicate that instructional leadership has a positive and significant effect on teachers’ teaching service, and the school environment also has a positive and significant effect. These variables explain a substantial proportion of the variance in teachers’ teaching service. Strengthening principals’ instructional leadership and systematically improving school environmental conditions are strategic efforts to enhance the quality of teachers’ teaching service and, in turn, to support the improvement of educational quality at the junior high school level.